EFEKTIVITAS SENAM OTAK TERHADAP KONSENTRASI BELAJAR PADA SISWA KELAS V DI YAYASAN PENDIDIKAN ISLAM ISTIQOMAH MEDAN TAHUN 2020 - Nila Hayati (Poltekkes Kemenkes Padang, 2021)
Brain exercise is a series of simple movements that help optimize the function of all kinds of centers in the human brain. The brain exercise method focuses on the use of movemment activities to draw out all one’s potential so that it is expected to facilitate blood flow and stretch nerves due to fatigue and stress of learning. The purpose of this study was to determine the effectiveness of brain exercise on learning concentration in grade V students at the Istiqomah Medan Islamic Education Foundation. This study used a quasi experimental research design with one group pretest-posttest designs. Analysis of data using the wilcoxon test. Population of 42 students, the sampling technique used a total population of 42 students. The results of data processing using the wilcoxon test obtained a p value of 0,000 < 0,05 then Ho is rejected and Ha is accepted. The conclusion is that there is the effectiveness of brain exercise on learning concentration in grade V students at the Istiqomah Medan Islamic Education Foundation. The suggestion from the reseacher is to recommend the teacher to intruct students to do brain exercises to increase learning concentration.